2015
DOI: 10.1016/s2213-2600(15)00458-0
|View full text |Cite
|
Sign up to set email alerts
|

Burden of transmitted multidrug resistance in epidemics of tuberculosis: a transmission modelling analysis

Abstract: BackgroundMultidrug-resistant tuberculosis (MDR-TB) can be acquired through de novo mutation during TB treatment or through transmission from other individuals with active MDR-TB. Understanding the balance between these two mechanisms is essential when allocating resources for MDR-TB.MethodsWe constructed a dynamic transmission model of an MDR-TB epidemic, allowing for both treatment-related acquisition and person-to-person transmission of resistance. We used national TB notification data to inform Bayesian es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
147
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 180 publications
(156 citation statements)
references
References 61 publications
8
147
0
1
Order By: Relevance
“…40,41 One study examined the estimated incidence of new and retreatment cases in countries with a high tuberculosis burden, and concluded that more than 95% of MDR tuberculosis is due to primary transmission of resistant strains. 42 Consistent with the results described above, these findings suggest that a focus on early detection and improved treatment of MDR tuberculosis is needed to curtail future incidence.…”
Section: Modelling Mdr Epidemicssupporting
confidence: 83%
See 4 more Smart Citations
“…40,41 One study examined the estimated incidence of new and retreatment cases in countries with a high tuberculosis burden, and concluded that more than 95% of MDR tuberculosis is due to primary transmission of resistant strains. 42 Consistent with the results described above, these findings suggest that a focus on early detection and improved treatment of MDR tuberculosis is needed to curtail future incidence.…”
Section: Modelling Mdr Epidemicssupporting
confidence: 83%
“…49,82,[99][100][101] In most regions of the world, drug-resistant tuberculosis is now predominantly caused by transmission rather than acquisition of resistance, with an estimated 95·9% of MDR tuberculosis in new tuberculosis cases and 61·3% in previously treated cases being due to transmission. 42 Even the epidemiology of XDR tuberculosis-defined as resistance to isoniazid, rifampicin, a fluoroquinolone, and an injectable agent-is now better understood as reflecting endemics rather than epidemics, 48,95,102,103 and population migration is recognised as a vehicle for spread beyond the region of the strain's origin. Indeed, molecular epidemiological studies have documented the spread of drug-resistant strains within countries, between countries, and even across con tinents (figure 3).…”
Section: Advantagesmentioning
confidence: 99%
See 3 more Smart Citations